Behavior management in afterschool settings. Issue 144 (December 2014) - Mahoney, Joseph L.
Abstract : Although behavioral management is one of the most challenging aspects of working in an afterschool setting, staff do not typically receive formal training in evidence‐based approaches to handling children's behavior problems. Common approaches to behavioral management such as punishment or time‐out are temporary solutions because they do not identify and change the factors causing the problematic behaviors. In some cases, these approaches increase or intensify undesirable behaviors. This chapter discusses one approach to behavioral management—functional behavior assessment—that research proves effective in eliminating or reducing the occurrence of behavior problems in educational settings.